2021
DOI: 10.1002/hep4.1886
|View full text |Cite
|
Sign up to set email alerts
|

The rs429358 Locus in Apolipoprotein E Is Associated With Hepatocellular Carcinoma in Patients With Cirrhosis

Abstract: The host genetic background for hepatocellular carcinoma (HCC) is incompletely understood. We aimed to determine if four germline genetic polymorphisms, rs429358 in apolipoprotein E ( APOE ), rs2642438 in mitochondrial amidoxime reducing component 1 ( MARC1 ), rs2792751 in glycerol‐3‐phosphate acyltransferase ( GPAM ), and rs187429064 in transmembrane 6 superfamily member 2 ( TM6SF2 ), previously associated with progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Significant associations have also been identified between rs72613567 in HSD17B13 and rs429358 in APOE and a reduced risk for developing HCC in ArC 9–11. In this study, these protective associations were confirmed but failed to reach a detectable genome-wide significance level (online supplemental table 5).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Significant associations have also been identified between rs72613567 in HSD17B13 and rs429358 in APOE and a reduced risk for developing HCC in ArC 9–11. In this study, these protective associations were confirmed but failed to reach a detectable genome-wide significance level (online supplemental table 5).…”
Section: Discussionmentioning
confidence: 57%
“…In recent years, interest has focused on dissecting the underlying host genetics of HCC through candidate gene association studies. In the studies undertaken to date, loci in the genes coding for patatin-like phospholipase domain containing 3 ( PNPLA3 ; rs738409) and transmembrane 6 superfamily member 2 ( TM6SF2; rs58542926) were robustly confirmed to increase the risk of developing HCC in ArC,8 while loci, rs72613567:TA in hydroxysteroid 17-beta dehydrogenase 13 ( HSD17B13 ) and rs429358:C in apolipoprotein E ( APOE ), were found to attenuate risk 9–11. As the products of these genes are involved in lipid turnover and processing, it is not surprising that the same loci also modulate the risk for HCC development in people with non-alcoholic fatty liver disease (NAFLD) 12…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the polymorphism of APOE has been investigated in liver cancer. Innes et al found that rs429358 of APOE is associated with a decreased risk of developing HCC in patients with liver cirrhosis (Innes et al, 2022). The E4 allele of APOE can function as a protective factor in reducing inflammation and liver fibrosis in HCV-infected patients, which may decrease the risk of liver cancer (Nascimento et al, 2021).…”
Section: Liver Cancermentioning
confidence: 99%
“…ApoE is present on the surface of lipoprotein particles and plays a key role in regulating lipid transport of the liver. Carrying ApoE is associated with a reduced risk of hepatocellular carcinoma that is causally related to liver metabolic disorders 22 . Thus, intense efforts have been made to investigate hepatic metabolism based on ApoE −/− mice 23–25 .…”
Section: Introductionmentioning
confidence: 99%
“…Carrying ApoE is associated with a reduced risk of hepatocellular carcinoma that is causally related to liver metabolic disorders. 22 Thus, intense efforts have been made to investigate hepatic metabolism based on ApoE −/− mice. [23][24][25] In addition, Narjes et al proved that Empagliflozin alleviates NAFLD in high-fat diet-fed ApoE −/− mice by reducing ER stress and activating autophagy.…”
Section: Introductionmentioning
confidence: 99%